Synthesis and functionalization of Si-MCM-41 with amines - Ramli, A. (Nova Science Publishers, Inc., 2013)
The Siliceous Mesoporous Molecular Sieve Si-MCM-41 was synthesized by the hydrothermal method at 100Â°C for 2-10 days. Results show that eight days duration is the optimum duration for the synthesis of Si-MCM-41 with highly ordered uniform hexagonal mesopores with Type IV isotherm and HI type hysteresis loop. The Si-MCM- 41 was then functionalized with 10-50wt of Monoethanolamine (MEA), Tetraethylenpentamine (TEPA) and Polyethylenimine (PEI). All the functionalized samples were characterized by XRD, FTIR, FESEM, HRTEM, N2 adsorption-desorption, TGA and elemental analysis. The physicochemical changes have been observed with a reduction in peak intensity in XRD diffractograms. Functional groups responsible for amine functionalization were observed in FTIR spectra. Agglomerated.particles were observed in FESEM micrographs. Hexagonal pores remained intact as observed in HRTEM images The adsorptiondesorption isotherms changed from Type IV to Type III by N2 adsorption-desorption. Each group showed different thermal stability observed by TGA and elemental analysis confirmed the presence of C and N in functionalized samples. Overall, results showed that Si-MCM-41 was successfully modified with Monoethanolamine, Tetraethylenpentamine and Polyethylenimine. Â© 2014 Nova Science Publishers, Inc.